PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA PEMESANAN SAYUR-MAYUR BERBASIS WEB PADA TOKO DAMAI REZEKI (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2025)
Damai Rezeki is one of the businesses engaged in the supplier of food raw materials, especially vegetables and seasoning spices and has a B2B or business-to-business type of business. The sales process is still written manually on bill of sales or in books and the sales reports are only stored as documents and archived. While these data and documents are very important for Damai Rezeki Store. To resolve or to prevent data becomes damaged or loss, it is necessary to create a program or a system that can maintain data and stored the data safely and can produce a report needed by Damai Rezeki Store. Based on the problems mentioned before, the authors designed a web-based data processing information system for ordering, using one of the PHP frameworks, CodeIgniter with SQL Server database.